FACTORS INFLUENCING SATISFACTION WITH SERVICE RECOVERY AND WORD-OF-MOUTH: AN EMPIRICAL STUDY OF BANKING INDUSTRY IN MALAYSIA - Nurbainy Susendra Mohd Anuar; Naheed Sultan; Muhammad Tahir Jan (International Journal of Accounting, Finance and Business, 2018)
Purpose - The purpose of this paper is to investigate the impact on external attributions, unstable attributions, uncontrollable attributions, service recovery efforts on customer satisfaction with service recovery. In addition, the paper also attempts to investigate the impact of customer satisfaction with service recovery on word-of-mouth intention. Design/methodology/approach – A self-administered questionnaire, adapted from previous studies, was distributed through convenience sampling method to those customers who had experienced service failures in the banks and had also afterwards complaints about that experience. A total of 350 questionnaires were distributed in order to collect data for the same purpose. Findings - The results show external attributions, unstable attributions, uncontrollable attributions, service recovery efforts have significant effects on customer satisfaction with service recovery. Moreover, there is also a significant positive impact of customer satisfaction with service recovery on word-of-mouth intentions. Practical implications – In the banking sector, service recovery is an important element in satisfying the customers. As a result, this study will assist the banks in achieving higher profit, higher market share and higher return by ensuring customer satisfaction when the complaints are heard and addressed. It will also generate positive word of mouth, which may eventually create a positive image of the banks. Originality/value – This paper is a unique attempt to understand the critical factors behind customer satisfaction with regard to service recovery, particularly in Malaysian banking industry. It also has many methodological and practical implications.